2015
DOI: 10.1186/s12913-015-0848-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographic and perceptual variables on a young adult’s decision to be covered by private health insurance

Abstract: BackgroundThe large number of uninsured individuals in the United States creates negative consequences for those who are uninsured and for those who are covered by health insurance plans. Young adults between the ages of 18 and 24 are the largest uninsured population subgroup. This subgroup warrants analysis. The major aim of this study is to determine why young adults between the ages of 18 and 24 are the largest uninsured population subgroup.MethodsThe present study seeks to determine why young adults betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
(34 reference statements)
2
27
1
Order By: Relevance
“…In a sense, these discordant behaviors suggest that engaging in high levels of healthy behaviors may lead to overconfidence that limit other areas of health-oriented action. For example, a strong cultural emphasis on personal responsibility may lead members of these groups to focus less on primary prevention or influence their decisions to carry health insurance ( Cantiello, Fottler, Oetjen, & Zhang, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a sense, these discordant behaviors suggest that engaging in high levels of healthy behaviors may lead to overconfidence that limit other areas of health-oriented action. For example, a strong cultural emphasis on personal responsibility may lead members of these groups to focus less on primary prevention or influence their decisions to carry health insurance ( Cantiello, Fottler, Oetjen, & Zhang, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The large variation in insurance coverage noted within the study population may be partially due to various eligibility criteria for public insurance in the United States. Other factors that affect insurance coverage include poverty, unemployment, and socioeconomic disadvantage . In addition, Stone et al revealed an association between insurance status and race or poverty in metropolitan and nonmetropolitan counties …”
Section: Discussionmentioning
confidence: 99%
“…Other factors that affect insurance coverage include poverty, unemployment, and socioeconomic disadvantage. 12,21,23 In addition, Stone et al revealed an association between insurance status and race or poverty in metropolitan and nonmetropolitan counties. 24…”
Section: Variations In Insurance Status In the Study Populationmentioning
confidence: 99%
“…Furthermore, a study of Australian health consumers found that consumers' choices are not grounded in their individual experiences of the system but their futuristic expectations of bene t and whom they trust to help them minimise risk [16]. In the United States, factors including perceived health status, perceived value, perceived need, socioeconomic status and ethnicity signi cantly affected whether U.S. young adults would enrol in PHI and that there was a combination of factors that affected their choices [17].…”
Section: Factors Affecting Phi Choices In Australiamentioning
confidence: 99%